True Entrepreneur versus False Entrepreneur: Implications for Family Business - Montiel, Oscar (Emerald Publishing, 2022)
Entrepreneurship and family businesses are fundamental factors in economic activity since, through the generation of new ideas, it is possible to generate new businesses that trigger employment, innovation, and economic growth. Recently, an emphasis on seeing both research streams from a kaleidoscope perspective has given new insights into the development and evolution of this area. Thus, exploring the differentiation between true and false entrepreneurs seems vital for today’s efficient allocation of resources. A theoretical model is proposed, including micro, meso, and macro analytical spheres, adding the behavioral aspects that determine whether a person is a true or false entrepreneur and the effects that can have on the business. To observe the viability of the approach, the case of an enterprise, called “family business S,” is examined. Specifically, the results show the feasibility of applying the analytical proposal to observe the positive and negative behaviors of the family business. In the case of S, these are false entrepreneurs, given that free time and unemployment were the main reasons for starting the company, but they lacked the will and long-term vision. Also, a novel view on how to diagnose a real entrepreneur for taking over a family business is proposed, where a clinical history approach might help in the succession process.